Impact of native vegetation cover near crops on the occurrence and molecular diversity of fire ants - Nagatani, Victor H.; Ramalho, Manuela O.; Alves, Juliana M. C.; Souza, Rodrigo F.; Kayano, Débora Y.; Silva, Nathalia S.; Silva, Otávio G. M.; Harakava, Ricardo; Bueno, Odair C. [UNESP]; Hilsdorf, Alexandre W. S.; Morini, Maria S. C. (Wiley, 2023)
Solenopsis invicta and Solenopsis saevissima are the most common fire ants in Brazil. Environmental disturbances favour the colony dispersal of both species, particularly those with an anthropogenic origin. However, the frequencies of the species can vary according to the amount of anthropogenic disturbances. Crops near native vegetation fragments is a common landscape in the Brazilian Atlantic Forest. Here, we analyse if there is influence of native vegetation cover on the occurrence of these fire ants and their molecular diversity in crops. Our hypothesis is that these species are antagonistic in terms of occurrence and molecular diversity when compared in the same habitat. We selected crops near fragments with around 50% of native vegetation cover, a percentage informative enough to detect biological responses from insects belonging to a same order. Nests were collected and the species were identified using external morphology, and mtDNA COI sequences. We reject our hypothesis, which suggest that the species colonize the vegetation patches around crops in a similar way. Solenopsis invicta is not limited by vegetation cover, and has a high haplotype diversity when compared to S. saevissima, particularly when the vegetation cover is greater than 50%. Additionally, the vegetation cover seems to not have influence in the total number of haplotypes, but the species have haplotypes that are exclusive to each landscape. Our findings suggest that S. invicta is expanding to native vegetation areas that it has not occupied before, as S. saevissima was dominant there.
Keywords: agricultural landscapes; anthropogenic disturbances; Atlantic Forest; genetic diversity; human-modified landscape; olericulture